Towards the quark gluon plasma via MHV techniques - Rabemananjara, Tanjona Radonirina (Department of Physics, 2019)
We study the multiple radiative gluon emission off a massless and highly energetic quark in the pQCD picture. We introduce the Maximally Helicity Violating (MHV) techniques to cope with the complexities in computing cross sections in multi-jet QCD. The multiphoton emission in QED is reviewed to emphasize the efficiency of the MHV approach. We show that the computation of the multiple photon emission current provides insight into the understanding of the multiple radiative gluon emission in QCD. We then compute the momentum distribution for one, two and three soft and collinear radiative gluons from a hard struck quark. Our MHV results exhibit non-Abelian information about the correlation of gluons. As a phenomenological analysis, we study the energy spectrum for emitting radiative gluons using our MHV results. By comparing the MHV and the standard Poisson approximation of uncorrelated multiple emission results, we see that there is significant difference between the two methods.